Transmigration of the left mandibular canine observed during 2 years in cone-beam computed tomography examination - Ingrid Rozylo-Kalinowska; Katarzyna Denkiewicz; Zofia Cecherz; T Katarzyna Różyło (Wolters Kluwer Medknow Publications, 2018)
Transmigration is considerably a rare preeruptive dislocation of an affected tooth across the midline. Cone-beam computed tomography (CBCT) is a relatively new technology in dentomaxillofacial radiology. The aim of the study is to present a case report of progressing transmigration in an 11-year-old girl examined by means of CBCT. A 9-year-old girl was referred for CBCT twice before and during orthodontic treatment. In the baseline examination, the impacted lower left canine was impacted and incorrectly positioned, but 9 months later, the canine had already crossed the midline. In conclusion, to the authors' best knowledge, this is the first case of observation of mandibular canine transmigration by means of CBCT that allows precise evaluation of the transmigrating tooth.